Enhancing Learning Outcomes through Peer Tutoring in ELT at STIFI BP Palembang - Eliza, Tiara (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
This exploration is persuaded by the presence of variables that impact the progress of English learning programs through peer coaching techniques in English subjects. The implementation of English learning using peer tutoring strategies is great since it will help the students in getting and understanding material all the more successfully. In addition, it provides tutors with an opportunity to enhance their skills. The achievement pace of the learning program utilizing peer tutor strategy is very high, where the students become more joyful, grasp the material better and are more adaptable while talking about with peers. This factor makes researcher interested in studying more deeply about how much influence and success of learning programs using peer tutor strategies on student understanding and abilities. This research focus on the implementation of using Peer Tutoring Strategy in English Learning at STIFI Palembang, then to depict the assessment of how the evaluation of Peer Tutoring Strategy in English Learning at STIFI Palembang. This study utilized qualitative descriptive design. The participants were taken from the students in English class. The research data is collected by using Questionnaire and Interview. There were 55 students selected as the subjects of study. The result showed that the improvement and enhancement of the students’ quiz score. There were two quiz sessions taken, the first was a quiz session without tutor, the second session was with the tutor. Therefore, the most common way of carrying out the process of implementing the peer tutoring strategy in English learning found that the tutees felt more agreeable and attractive in learning English. The students who get help are more effective in receiving material. At the same time, for tutors, it is an opportunity to develop their abilities. The tutees become happier, understand the material better and are more flexible when discussing with peers without hesitates. The students who get help are more effective in receiving material. At the same time, for tutors, it is an opportunity to develop their abilities. Therefore this strategy benefits to students, tutors, and teachers by emphasizing activeness, understanding, and cooperation during learning.